Exploring undergraduate EFL students’ perceptions on the use of Duolingo application in enhancing vocabulary (Journal of Academic Research, 2024)
This study aims to explore undergraduate students’ perceptions on the use of Duolingo application in learning English language vocabulary. A mixed-methods study was used; data were collected through a questionnaire and a semi-structured interview. 90 students from the English department at Sabratha University participated in the study. The results indicate that students are willing and ambitious to use Duolingo application to learn a language and particularly vocabulary as it is easy, convenient and effective in an encouraging way that can motivate learning. Their reaction towards the application was overall positive and Duolingo can promote learning and developing vocabulary, but there are some limitations. However, there is no significant difference between students’ academic level and their perception toward Duolingo application. Language learning applications are great tools to improve knowledge of a new language thus, it is recommended to encourage language learners of different levels to use Duolingo.
Keywords: Duolingo Application; vocabulary; EFL